Análise do diagnóstico de enfermagem obesidade em indivíduos com diabetes mellitus tipo 2 - BARROS, Eremilta Silva (2023)
This study aims to analyze the Nursing Diagnosis (ND) obesity in individuals with Type 2 Diabetes Mellitus (DM2). This is a cross-sectional analytical study, developed at the Presidente Dutra University Hospital, in São Luís-MA, from January to June 2022. Those aged over 18 years or older and diagnosed with DM2 were included, and individuals with edema, wheelchair users, were excluded from the study due to the unavailability of an appropriate scale in the unit for weighing in this condition; and those with difficulty in verbal communication. For the collection of data from the participants, a collection instrument was used, with sociodemographic, anthropometric, clinical data and to assess the presence or absence of related factors and the defining characteristic of the nursing diagnosis of obesity, some questions and scales were used, validated questionnaires such as the International Physical Activity Questionnaire (IPAQ) - short version, SCOFF Questionnaire - BR, EPWORTH Sleepiness Scale - ESE-BR, Mini - Sleep Questionnaire (MQS), International Physical Activity Questionnaire (IP AQ) short version. Descriptive and inferential analyses, t-Test, Fisher's Exact Test, Odds Ratio, and the logistic regression model were applied for analysis, to identify the variables that are related to the nursing diagnosis of obesity, the analyzes were performed using the statistical software R.The study was approved by the Research Ethics Committee of the Presidente Dutra University Hospital, under opinion number 4,853,304. Most of the 249 interviewees had a mean age of 56.8 years, declared themselves brown, female, had a partner, had more than four years of education, reported self-employment, had an income lower than the minimum wage and had DM2 for 6-10 years, did not carry out periodic control of capillary blood glucose at home in the sample, had capillary blood glucose on the day of the interview from 126 to 199 mg/dl, and reported having more than 3 meals a day. Furthermore, there was a sedentary behavior of the participants according to the international physical activity questionnaire short version (IPAQ - short version). The defining characteristic of the Nursing Diagnosis obesity BMI  30, which classifies the individual with obesity, presented a percentage prevalence of 30.5% in the study participants. When evaluating the related factors, it was found that those that were associated with the nursing diagnosis of obesity were: disorganized eating behaviors (OR = 3.51) and energy expenditure below energy intake (OR = 6.49). It is concluded that the nursing diagnosis of obesity was more prevalent among study participants. The related factors that were associated with obesity in individuals with Type 2 Diabetes Mellitus were the presence of disorganized eating behaviors and energy expenditure below energy intake. It is believed that the findings will contribute to the planning of actions and improvement of nursing care for the individual with this diagnosis and diabetes mellitus 2.